Nomenclatural and Taxonomic Novelties in Senecio ser. Corymbosi (Asteraceae, Senecioneae) from Southern South America - López, Mariana Gabriela (2010)
The new name, subseries Alcabrerae M. G. Lopez, A. F. Wulff & Xifreda for Senecio L. ser. Corymbosi (Cabrera) Cabrera, is here proposed to replace Senecio subsect. Amplectentes Cabrera. Although the name Amplectentes was published at different subgeneric ranks within the genus Senecio (Asteraceae, Senecioneae), the use of the same epithet is considered homonymy according to the International Code of Botanical Nomenclature, Article 53.4 and Article 21, Note 1. Additionally, S. saucensis Cabrera, one of the five species belonging to Senecio subser. Alcabrerae, is synonymized with S. toroanus Cabrera, formerly assigned to Senecio ser. Hualtatini DC., and S. toroanus is transferred to subseries Alcabrerae. The micromorphology of the cypselae for both species is provided, in support of the synonymy.